Sticky rebates: rollback rebates induce non-rational loyalty in consumers ; experimental evidence - Alexander Morell; Andreas Glöckner; Emanuel Vahid Towfigh (Max Planck Institute for Research on Collective Goods, 2009)
We investigate whether and how targeted rebates impede rational switching of consumers from an incumbent to an outside option (e.g., market entrant). In a real trading problem, participants repeatedly buy tokens and can enter a target rebate scheme. Buying in a rebate scheme considerably reduces the likelihood that they switch to a higher-payoff outside option later. We conclude that targeted rebates might have an underestimated potential to foreclose consumer markets. The stickiness effect increases with the increasing number of previous buying in the rebate scheme, but not with the size of the rebate. Prospect Theory can partially account for these effects.
Keywords: 330; Rabatt; Konsumentenverhalten; Customer Relationship Management; Wechselkosten; Prospect Theory; Test